Arish : palm-leaf architecture - Piesik, Sandra (London : Thames & Hudson, 2012)
This is an in-depth, vibrantly illustrated survey of palm-leaf architecture: its history and traditions, its present and its future. Traditional buildings made from the leaves of date palms have provided shelter from the extreme climate of the Arabian peninsula for centuries. In many regions this is referred to as Arish. The book contains five sections: an overview in historical photographs; a comparison of regional variations in the United Arab Emirates; a focus on architectural and stylistic details; contemporary applications; and a resources section, including a step-by-step introduction to the making of Arish, from raw material to built form. Sandra Piesik, who has worked extensively in the United Arab Emirates, celebrates this unique, indigenous building and craft tradition and provides the foundation for a genuine understanding of the region, critical in the context of the fast-developing global economy it has become today. -- Publisher Description.
Includes bibliographical references.
Keywords: Date palm fiber -- United Arab Emirates; Plant fibers as building materials -- United Arab Emirates; Vernacular architecture -- United Arab Emirates